2017
DOI: 10.1002/pbc.26777
|View full text |Cite
|
Sign up to set email alerts
|

Chronic steroid‐response pancytopenia and increased bone density due to thromboxane synthase deficiency

Abstract: Diagnosis of bone marrow failure (BMF) disorders is challenging but essential for optimal patient management. Here, we report a young adult from nonconsanguineous parents with progressive pancytopenia since childhood, bone pain, increased bone density, and haphazard ossification replacing hematopoiesis within the bone marrow. Sequencing revealed two novel biallelic variants of unknown significance within the thromboxane A synthase gene, TBXAS1 (c.266T > C; c.989T > C), bioinformatically predicted to disrupt th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Elevated PGE2 may suppress erythroid precursor cells, resulting in refractory anemia seen in GHDD patients. It is also suggested that TXAS and TXA2 may also play a key role in bone remodeling as PGE2 that can stimulate both bone resorption and formation 2,7,8 . Progressive diaphyseal dysplasia (PDD) also known as Camurati-Engelmann disease is a close radiologic differential diagnosis of GHDD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PGE2 may suppress erythroid precursor cells, resulting in refractory anemia seen in GHDD patients. It is also suggested that TXAS and TXA2 may also play a key role in bone remodeling as PGE2 that can stimulate both bone resorption and formation 2,7,8 . Progressive diaphyseal dysplasia (PDD) also known as Camurati-Engelmann disease is a close radiologic differential diagnosis of GHDD.…”
Section: Discussionmentioning
confidence: 99%
“…Severe congenital neutropenia (SCN) patients are affected by congenital severe neutropenia, with an absolute neutrophil count (ANC) of less than 0.2 × 10 9 /L [ 115 ]. Bone marrow examination in the majority of cases reveals a maturation arrest of myelopoiesis at the level of promyelocytes, which generally leads to reduced neutrophil counts but increased numbers of atypical promyelocytes.…”
Section: Hematological Rare Disodersmentioning
confidence: 99%
“…Bone marrow examination in the majority of cases reveals a maturation arrest of myelopoiesis at the level of promyelocytes, which generally leads to reduced neutrophil counts but increased numbers of atypical promyelocytes. In these patients, the risk of infections such as otitis, gingivitis, skin infections, pneumonia, deep abscesses and septicemia begins in the neonatal period [ 115 ]. Furthermore, patients with severe congenital neutropenia have an increased risk of developing leukemia [ 115 ] .…”
Section: Hematological Rare Disodersmentioning
confidence: 99%
See 2 more Smart Citations